STUDENTS’ PERCEPTIONS ABOUT THE ONLINE LISTENING COURSES DURING THE COVID-19 PANDEMIC - Salsabila Gita Nurani; Utami Widiati (University of Muhammadiyah Malang, 2021)
The COVID-19 pandemic that has spread worldwide has recently changed many aspects of human life, including education. Since this pandemic requires every level of education to conduct the teaching and learning classes in online courses, all education aspects perceive the benefits and even the difficulties through this online course method. This study aimed at knowing the undergraduate students' perceptions about the online listening courses during the COVID-19 pandemic, focusing on the benefits and the difficulties of joining the courses. This survey study involved 74 undergraduate English students of a private university in Malang, Indonesia. An online questionnaire was distributed to the students via Google Form link, consisting of 30 statements with 4-scales of the Likert scale (strongly disagree, disagree, agree, strongly agree). All questionnaire items were valid at the .05 level and were highly reliable with a coefficient of .955. The average value of each item was then measured to reflect positive or negative perceptions. The findings showed that the students perceived positively not only to online listening courses' method but also the difficulties of the method. It means they agreed that online listening courses could be beneficial in this pandemic condition, but they also still have several difficulties joining it. Lastly, this research suggests further researchers use a mix-method research design in which they can include open-ended interviews to get deeper analysis.